2022
DOI: 10.4269/ajtmh.21-0568
|View full text |Cite
|
Sign up to set email alerts
|

Talaromyces marneffei Influences Macrophage Polarization and Sterilization Ability via the Arginine Metabolism Pathway in Vitro

Abstract: The opportunistic fungal pathogen Talaromyces marneffei, which is endemic across a narrow band of tropical Southeast Asia and southern China, is an intracellular pathogen that causes systemic and lethal infection through the mononuclear phagocyte system. The mechanisms by which T. marneffei successfully replicates and escapes the immune system remain unclear. To investigate the role of arginine metabolism in the escape of T. marneffei from killer macrophages, we assessed inducible nitric oxide synthase (iNOS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The expression of CD86 is increased in the majority of early infection phases. However, compared to cells cultured alone, our earlier research indicated that the expression level of CD86 in macrophages was dramatically reduced, while the quantity of CD86 in the supernatant was significantly increased 11,12 . An important question that needs to be investigated is the role of CD86 in macrophage infection with T. marneffei ?…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The expression of CD86 is increased in the majority of early infection phases. However, compared to cells cultured alone, our earlier research indicated that the expression level of CD86 in macrophages was dramatically reduced, while the quantity of CD86 in the supernatant was significantly increased 11,12 . An important question that needs to be investigated is the role of CD86 in macrophage infection with T. marneffei ?…”
Section: Discussionmentioning
confidence: 97%
“…However, compared to cells cultured alone, our earlier research indicated that the expression level of CD86 in macrophages was dramatically reduced, while the quantity of CD86 in the supernatant was significantly increased. 11 , 12 An important question that needs to be investigated is the role of CD86 in macrophage infection with T. marneffei ? Many pattern recognition receptors of macrophages can directly interact with fungi, leading to the production of macrophage inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations